A pan-cancer and single-cell sequencing analysis of CD161, a promising onco-immunological biomarker in tumor microenvironment and immunotherapy - Li, He; Zhou, Ke; Wang, Kaiyue; Cao, Hui; Wu, Wantao; Wang, Zeyu; Dai, Ziyu; Chen, Shi; Peng, Yun; Xiao, Gelei; Luo, Peng; Zhang, Jian; et al. (Frontiers in Immunology, 2022)
Background: CD161 is closely related to the occurrence and development of various cancers. Methods: The mutation map and the variation of CNVs and SNVs of CD161 were displayed according to cBioportal and GSCALite. We also evaluated the pathway enrichment and drug sensitivity of CD161 according to GSCALite. We performed a single-cell sequencing analysis of cancer cells and T cells in melanoma. The cell communication patterns related to CD161 were further explored. The expression of CD161 in macrophages and T cells was detected using multiplex immunofluorescence staining of tissue microarrays. Results: A high CD161 level was related to neoantigens expression, pathway enrichment, and drug sensitivity. In addition, single-cell sequencing analysis revealed that CD161 was mainly expressed in T cells, M1 and M2 Macrophages, neoplastic, microglial cells, neurons, and cancer cells in many tumor types. Further study on pseudotime trajectories and functional annotation of CD161 proved the critical role of CD161 in tumor progression and T cell immunity in melanoma. Multiplex immunofluorescence revealed that CD161 is closely correlated with the immune infiltration of T cells and macrophages in multiple cancers. In addition, high CD161 expression predicted a favorable immunotherapy response. Conclusion: CD161 is involved in the immune infiltration of T cells and macrophages and might be a promising target for tumor immunotherapy.